Adrenergic System Activation Mediates Changes in Cardiovascular and Psychomotoric Reactions in Young Individuals after Red Bull© Energy Drink Consumption - Ana Cavka; Marko Stupin; Ana Panduric; Ana Plazibat; Anita Cosic; Lidija Rasic; Zeljko Debeljak; Goran Martinovic; Ines Drenjancevic (International Journal of Endocrinology)
Objectives. To assess the effect of Red Bull© on (1) blood glucose and catecholamine levels, (2) cardiovascular and respiratory function changes before, during, and after exercise, (3) reaction time, (4) cognitive functions, and (5) response to mental stress test and emotions in young healthy individuals (N=38). Methods. Heart rate (HR) and arterial blood pressure (ABP), blood glucose, adrenaline, and noradrenalin plasma levels were measured before and after Red Bull© intake. Participants were subjected to 4 different study protocols by randomized order, before and 30 minutes after consumption of 500 mL of Red Bull©. Results. Mean ABP and HR were significantly increased at rest after Red Bull© intake. Blood glucose level and plasma catecholamine levels significantly increased after Red Bull© consumption. Heart rate, respiration rate, and respiratory flow rate were significantly increased during exercise after Red Bull© consumption compared to control condition. Intake of Red Bull© significantly improved reaction time, performance in immediate memory test, verbal fluency, and subject’s attention as well as performance in mental stress test. Conclusion. This study demonstrated that Red Bull© has beneficial effect on some cognitive functions and effect on cardiovascular and respiratory system at rest and during exercise by increasing activity of the sympathetic nervous system.